Strategi pengembangan infrastruktur pendidikan AI: Kesiapan sekolah menengah atas atau kejuruan di Kabupaten Manggarai Barat - Elisabet Oktaviani Hanggu; Ludgardis Deliman (Curricula: Journal of Curriculum Development, 2026)
The rapid development of Artificial Intelligence (AI) has brought significant opportunities and challenges to the education sector, particularly in regions with limited infrastructure. This study aims to analyze the readiness of AI-supporting infrastructure in senior high schools and vocational schools (SMA/SMK) in West Manggarai Regency, focusing on the availability of facilities and infrastructure, the preparedness of human resources, and the challenges and strategies for AI implementation in education. This research employed a qualitative descriptive approach and was conducted in six SMA/SMK located in Labuan Bajo city and Lembor District. Data were collected through in-depth interviews, participatory observation, and documentation, and were analyzed thematically using the Miles and Huberman model. The findings indicate a significant disparity in AI infrastructure readiness between schools in Labuan Bajo and those in Lembor District. Schools in Labuan Bajo demonstrate relatively adequate digital infrastructure, competent human resources, and strong institutional support. In contrast, schools in Lembor face limitations in digital facilities, internet access, and teachers' AI-related competencies. The study concludes that successful AI integration in education requires equitable infrastructure development, continuous teacher capacity building, supportive school leadership, and strong collaboration between government, schools, and higher education institutions.